A Rapid and Sensitive Test for Diagnosing Heparin-Associated Thrombocytopenia - Greinacher, A; Michels, I; Kiefel, V; Mueller-Eckhardt, C (Thrombosis and Haemostasis, 1991)
Heparin-associated thrombocytopenia (HAT) is a severe complication of heparin therapy. Its diagnosis is difficult. Conventional assays employ platelet aggregometry (PAA) and/or 14C-serotonin release (SRA) which are either insensitive (PAA) or require radioactive tracers (SRA). We here describe a newly developed sensitive and rapid assay based on visual evaluation of heparin-induced platelet activation (HIPA) in microtiter wells. Using sera of 34 patients with clinically suspected HAT we found the HIPA assay to be as sensitive as the SRA and superior to PAA. The HIPA assay allows investigation of crossreactivity with different types of heparins, low molecular weight (LMW) heparins and heparinoids. Three patients who required further parenteral anticoagulation and in whom the HIPA assay was negative before treatment with the LMW heparinoid Org 10172, were treated with this new heparinoid without adverse reactions. We conclude that the HIPA assay may be a useful tool for differential diagnosis and therapy in patients with HAT.